Kajian Program Pengembangan dan Pemberdayaan Masyarakat di Bidang Kemandiriaan Ekonomi dan Sosial Budaya - DWIJAYA, Moh. Dika; Partama Misdiyanta,; Laura Puspita Sari, (ReTII, 2021)
Mining business license area of ​​PT. XYZ is one of them located in Palu City, Central Sulawesi Province. As a form of effort to reduce the impact of mining activities, it is necessary to have the role of the community to support the company in an effort to reduce the negative impacts that arise. The purpose of this research is to examine the community development and empowerment program as well as to examine the success of the community development and empowerment program in two fields, namely economic independence and socio-cultural independence. This research was conducted by distributing questionnaires to the community around the mining area. Samples were taken at simple random sampling with a total sample of 90 respondents. The sample testing method in this study was carried out in several stages, namely normality test and continued with score interpretation to determine the extent of the community development and empowerment program that the company had carried out. The results of the research that have shown that the program in the field of economic independence gets a "good enough" category with a value of 56.125%, and for the socio-cultural field it has a "quite good" result with a value of 59.25%. Keywords: Mining, economy, social, development, empowerment